Sulfation Patterns of Saccharides and Heavy Metal Ion Binding. Issue 52 (28th July 2019) - Alshanski, Israel; Blaszkiewicz, Joanna; Mervinetsky, Evgeniy; Rademann, Jörg; Yitzchaik, Shlomo; Hurevich, Mattan
Abstract: Sulfated saccharides are an essential part of extracellular matrices, and they are involved in a large number of interactions. Sulfated saccharide matrices in organisms accumulate heavy metal ions in addition to other essential metal ions. Accumulation of heavy metal ions alters the function of the organisms and cells, resulting in severe and irreversible damage. The effect of the sulfation pattern of saccharides on heavy metal binding preferences is enigmatic because the accessibility to structurally defined sulfated saccharides is limited and because standard analytical techniques cannot be used to quantify these interactions. We developed a new strategy that combines enzymatic and chemical synthesis with surface chemistry and label‐free electrochemical sensing to study the interactions between well‐defined sulfated saccharides and heavy metal ions. By using these tools we showed that the sulfation pattern of hyaluronic acid governs their heavy metal ions binding preferences. Abstract : Pattern recognition : The effect of sulfation patterns on the metal binding properties of saccharides is enigmatic because the accessibility to structurally defined sulfated saccharides is limited and because of the absence of suitable analytical techniques. Herein, electrochemical methods are used to show that the sulfation pattern of hyaluronic acid governs their heavy metal ions binding preferences (see scheme).